2020
DOI: 10.1007/s10834-020-09694-9
|View full text |Cite
|
Sign up to set email alerts
|

Families’ Financial Stress & Well-Being: The Importance of the Economy and Economic Environments

Abstract: The Great Recession and the unfolding COVID-19 Pandemic Recession-two major disruptions to the economy that occurred just one decade apart-unequivocally confirm the importance of the economy and economic environments for understanding families' financial stress and well-being. However, recent published literature places too little emphasis on the economy and economic environments and instead focuses on explanations rooted within individuals and families. In this article, we review research on families' financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 92 publications
(225 reference statements)
3
61
0
Order By: Relevance
“…In this study, debt delinquency refers to being late in debt repayment (Xiao & Yao, 2014). Researchers use different terms for perceived financial difficulties such as financial anxiety, stress, or distress (Archuleta et al, 2013;Friedline et al, 2020;Serido et al, 2014a). To be consistent with the literature of family economics, we use financial stress defined as a psychological state worrying about personal finance.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, debt delinquency refers to being late in debt repayment (Xiao & Yao, 2014). Researchers use different terms for perceived financial difficulties such as financial anxiety, stress, or distress (Archuleta et al, 2013;Friedline et al, 2020;Serido et al, 2014a). To be consistent with the literature of family economics, we use financial stress defined as a psychological state worrying about personal finance.…”
Section: Introductionmentioning
confidence: 99%
“…The result of a study by Mohammadi et al showed that lack of access to medical equipment for caregivers made caring for COVID-19 patients a challenge [34]. Also, highcost for covid-19 treatment has affected families' nancial stress and well-being, where the immediate and long-term effects of COVID-19 have led to occupational vulnerability of families because of unemployment, declining incomes, debt, and economic hardship [35].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor related to stress and well-being is the individual’s financial situation [ 100 ]. Being on sick- leave normally entails that one’s income is reduced, sometimes drastically, which most likely leads to stress for a majority of individuals, not only related to the current situation, but also to an uncertain economic future.…”
Section: A Proposed Cognitive Behavioral Explanatory Model Of Clinmentioning
confidence: 99%